2005
DOI: 10.1167/iovs.05-0105
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of IRS-1 Expression Causes Inhibition of Corneal Angiogenesis

Abstract: Subconjunctival injections of IRS-1 antisense ODN significantly inhibit rat corneal neovascularization. This effect may be mediated by a downregulation of IL-1beta. IRS-1 proteins may be interesting targets for the regulation of angiogenesis mediated by insulin, hypoxia, or inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Partial IRS-1 inhibition by GS-101 induced a significant inhibition of both VEGF-A and interleukin-1β transcription in cultured human endothelial cells associated with complete inhibition of capillary-like tube formation [17], an in vitro model of angiogenesis. Accordingly, topical administration of GS-101 in the injury-induced corneal neovascularization rat model inhibited in vivo angiogenesis [17, 18]. The results of this ‘first-in-man’ open-label Phase I tolerability study reported here demonstrate that GS-101 is well tolerated in healthy human subjects.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Partial IRS-1 inhibition by GS-101 induced a significant inhibition of both VEGF-A and interleukin-1β transcription in cultured human endothelial cells associated with complete inhibition of capillary-like tube formation [17], an in vitro model of angiogenesis. Accordingly, topical administration of GS-101 in the injury-induced corneal neovascularization rat model inhibited in vivo angiogenesis [17, 18]. The results of this ‘first-in-man’ open-label Phase I tolerability study reported here demonstrate that GS-101 is well tolerated in healthy human subjects.…”
Section: Discussionmentioning
confidence: 80%
“…IRS-1 involvement in angiogenesis has been demonstrated in vitro and in animal experiments, and the ability of GS-101 to inhibit IRS-1 has been validated [17, 18]. Previous in vitro investigations have shown that GS-101 inhibits IRS-1 expression in human endothelial cells placed under different angiogenic stimuli [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, IRS-1 over-expression was attributed to increased angiogenesis in human EC in association with increased Akt and VEGF-A expression [12], whilst in vivo , antisense IRS-1 sequences delivered by sub-conjunctival injection inhibited rat corneal neovascularisation [21], and when delivered by means of eye-drops (GS-101) were found to be tolerable in a phase-1 clinical trial and may be sufficient to prevent neovascularisation in disease such as retinopathy and neovascular glaucoma [22]. Therefore, IRS-1 represents a potent modulator of pro-angiogenic signalling cascades in vascular EC and as such, since we have shown both in vitro , and in the rat model of temporary MCAO that citicoline induces phosphorylation of IRS-1 and concomitant EC activation and increased vascularisation, this could be a key novel mechanism of action of citicoline.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of VEGF-A and VEGF-B to VEGFR-1 and VEGFR-2 induces hemangiogenesis [6][7][8]. In addition, the cytokines platelet-derived growth factor (PDGF) [9], fibroblast growth factor-2 (FGF-2), placental growth factor (PIGF), hepatocyte growth factor (HGF) [10] and the adapter protein insulin receptor substrate-1 (IRS-1) [11] have also been found to induce hemangiogenesis.…”
Section: Endogenous Regulators Of (Lymph)angiogenesismentioning
confidence: 99%